Expression of flavodiiron protein rescues defects in electron transport around PSI resulting from overproduction of Rubisco activase in rice. (2nd February 2022) - Suganami, Mao; Konno, So; Maruhashi, Ryo; Takagi, Daisuke; Tazoe, Youshi; Wada, Shinya; Yamamoto, Hiroshi; Shikanai, Toshiharu; Ishida, Hiroyuki; Suzuki, Yuji; Makino, Amane
Abstract : Overproduction of Rubisco activase disturbs electron transport around PSI and increases its susceptibility to photoinhibition, but these defects are rescued by expression of the flavodiiron protein in rice plants. Abstract: Fragility of photosystem I has been observed in transgenic rice plants that overproduce Rubisco activase (RCA). In this study, we examined the effects of RCA overproduction on the sensitivity of PSI to photoinhibition in three lines of plants overexpressing RCA ( RCA -ox). In all the RCA -ox plants the quantum yield of PSI [ Y (I)] decreased whilst in contrast the quantum yield of acceptor-side limitation of PSI [ Y (NA)] increased, especially under low light conditions. In the transgenic line with the highest RCA content ( RCA -ox 1), the quantum yield of PSII [ Y (II)] and CO2 assimilation also decreased under low light. When leaves were exposed to high light (2000 μmol photon m −2 s −1 ) for 60 min, the maximal activity of PSI ( P m ) drastically decreased in RCA -ox 1. These results suggested that overproduction of RCA disturbs PSI electron transport control, thus increasing the susceptibility of PSI to photoinhibition. When flavodiiron protein (FLV), which functions as a large electron sink downstream of PSI, was expressed in the RCA -ox 1 background ( RCA - FLV ), PSI and PSII parameters, and CO2 assimilation were recovered to wild-type levels. Thus, expression of FLV restored the robustness of PSI in RCA -ox plants.